Fields of dreams or diamonds in the rough: unconventional retirement migration - Bolender, Benjamin C. (Kansas State University, 2010)
Retirement age migration is not new. However, it has recently been garnering the attention of both researchers and local policy makers. Older migrants present the possibility of economic stimulus without creating additional pressure on the labor market. That said, a majority of works on retirement migration come to the same conclusions. Conventional theories state that older people move to places based on natural amenities and recreation opportunities. Further, these findings are often utilize a binary dependent variable based on whether a county has achieved a certain level of growth from inmigration of all people age 60+. I argue that this view is too narrow. Older age migrants move for a variety of reasons. These motives also vary across different age, sex, and race-ethnicity characteristics of the migrants in question. Further, not all counties that attract older migrants have bountiful natural or recreation amenities. Not only have these unconventional retirement destinations (URDs) had different historical trajectories, they also possess a different kind of amenities that appeal to older people who have relocated to the area. Finally, a focus on binary retirement classifications misses both diversity in retirement patterns and fails to explicitly account for the influence of space in county desirability. The goal of this work is to address these issues. First, I discuss the history and theories of retirement migration. Second, I develop models accounting for variation across older age migrant groups with varying demographic characteristics. Third, I identify and describe URD counties. Fourth, I present the results of a small-scale survey, community leader interviews, and a new model with additional variables to get at what other kinds of things should be labeled as “amenities.” Finally, I examine the role of space in migration research. My analysis demonstrates that there is much to be learned from looking at spatial models, micro-regional effects, and relative advantage between neighboring counties. Results indicate that conventional theories of retirement migration, while not necessarily wrong, are at least incomplete. The addition of diversity, new amenities, and space may greatly enhance our understanding of older age migration and migration research as a whole.
Keywords: aging; migration; spatial statistics; retirement; unconventional retirement migration (URD); retirement destination; Gerontology (0351); Sociology, Demography (0938); Urban and Regional Planning (0999)